C-reactive protein, immunoglobulin G and complement co-localize in renal immune deposits of proliferative lupus nephritis. (May 2013) - Sjöwall, Christopher; Olin, Anders I.; Skogh, Thomas; Wetterö, Jonas; Mörgelin, Matthias; Nived, Ola; Sturfelt, Gunnar; Bengtsson, Anders A.
<x xml:space="preserve">Abstract</x> The pattern recognition molecules C-reactive protein (CRP) and C1q are of big interest in relation to the pathogenesis of systemic lupus erythematosus (SLE). Circulating autoantibodies against CRP and C1q are frequently found in SLE patients with active disease, particularly in lupus nephritis (LN), and rising levels reportedly relate to disease activity and outcome. If CRP-, or dsDNA- and/or C1q-containing immune complexes (ICs) are pathogenic in LN, glomerular IgG-deposits would be expected to co-localize with these antigens. In search for proof of this concept, renal biospsies from patients with active LN (n = 5) were examined with high-resolution immunogold electron microscopy. Renal biopsies from patients with Henoch-Schönlein purpura, pauci-immune nephritis and renal cancer served as controls. IgG antibodies against CRP, C1q and nucleosomes were analyzed in pre–post flare sera. We could demonstrate that CRP, C1q, C3c and dsDNA were co-localized with IgG in electron dense deposits in the glomerular basement membrane/subendothelial space in all of the 5 LN patients. Deposits of IgG, CRP, complement and dsDNA were 10-fold higher in LN compared to controls. All SLE patients had circulating anti-nucleosome antibodies; 4/5 had serum antibodies against CRP, dsDNA, and C1q at biopsy/flare. Despite a limited number of cases, the results support the notion of a pathogenic role not only for anti-dsDNA antibodies, but also for anti-CRP and anti-C1q in LN. The glomerular ICs may have been generated by deposition of circulating ICs or by in situ IC formation.